First-in-man histotripsy of hepatic tumors: the THERESA trial, a feasibility study. (31st December 2022) - Vidal-Jove, Joan; Serres, Xavier; Vlaisavljevich, Eli; Cannata, Jon; Duryea, Alex; Miller, Ryan; Merino, Xavier; Velat, Manuela; Kam, Yossi; Bolduan, Ryan; Amaral, Joseph; Hall, Timothy; et al.
Abstract: Rationale Current hepatic locoregional therapies are limited in terms of effectiveness and toxicities. Given promising pre-clinical results, a first in-human trial was designed to assess the technical effectiveness and safety profile of histotripsy, a noninvasive, non-thermal, non-ionizing focused ultrasound therapy that creates precise, predictable tissue destruction, in patients with primary and secondary liver tumors. Methods A multicenter phase I trial (Theresa Study) was performed in a single country with 8 weeks of planned follow-up. Eight of fourteen recruited patients were deemed eligible and enrolled in the study. Hepatic histotripsy, was performed with a prototype system (HistoSonics, Inc., Ann Arbor, MI). Eleven tumors were targeted in the 8 patients who all had unresectable end-stage multifocal liver tumors: colorectal liver metastases (CRLM) in 5 patients (7 tumors), breast cancer metastases in 1 (1 tumor), cholangiocarcinoma metastases in 1 (2 tumors), and hepatocellular carcinoma (HCC) in 1 (1 tumor). The primary endpoint was acute technical success, defined as creating a zone of tissue destruction per planned volume assessed by MRI 1-day post-procedure. Safety (device-related adverse events) through 2 months was a secondary endpoint. Results The 8 patients had a median age of 60.4 years with an average targeted tumor diameter of 1.4 cm. The primary endpoint was achieved in all procedures. The secondary safety profile endpoint identified no device-related adverse events. Two patients experienced a continuous decline in tumor markers during the eight weeks following the procedure. Conclusions This first-in-human trial demonstrates that hepatic histotripsy effectively destroys liver tissue in a predictable manner, correlating very well with the planned histotripsy volume, and has a high safety profile without any device-related adverse events. Based on these results, the need for more definitive clinical trials is warranted. Trial Registration: Study to Evaluate VORTX Rx (Theresa). NCT03741088. https://clinicaltrials.gov/ct2/show/NCT03741088 KEY POINTS: Histotripsy, a new noninvasive, non-thermal, non-ionizing focused ultrasound therapy, safely created a zone of tissue destruction in the liver that correlated very well with the pre-defined planned tissue destruction volume. In this first human trial histotripsy was well tolerated with no histotripsy device-related adverse events and its primary endpoint of acute technical success was achieved in all 8 enrolled patients with primary or secondary liver tumors. This new locoregional therapy for patients with liver tumors is safe and effective, warranting further trials.